Characteristics and long-term catheter ablation outcome in long-standing persistent atrial fibrillation patients with non-pulmonary vein triggers. (15th August 2017) - Hung, Yuan; Lo, Li-Wei; Lin, Yenn-Jiang; Chang, Shih-Lin; Hu, Yu-Feng; Chung, Fa-Po; Tuan, Ta-Chuan; Chao, Tze-Fan; Liao, Jo-Nan; Walia, Rohit; Te, Abigail Louise D.; Yamada, Shinya; et al.
Abstract: Background: There are limited literatures regarding the non-pulmonary vein (NPV) triggers in long-standing persistent atrial fibrillation (LSPAF). The goal of the present study was to investigate the characteristics and long-term outcome of catheter ablation among these patients. Methods: The study included 776 patients (age 53.59 ± 11.38 years-old, 556 males) who received catheter ablation for drug-refractory atrial fibrillation (AF). We divided these patients into 3 groups. Group 1 consisted of 579 patients with paroxysmal AF (PAF), group 2 consisted of 103 patients with persistent AF (PerAF) and group 3 consisted of 94 patients with long-standing persistent AF (LSPAF). The average follow-up duration was 28.53 ± 23.21 months. Results: The clinical endpoint was the recurrence of atrial tachyarrhythmia. Among these 3 groups, higher percentages of male (93.6%, P < 0.001), NPV triggers (44.7%, P < 0.001), longer AF duration (6.65 ± 6.72 years, P = 0.029), larger left atrium diameter (44.44 ± 6.79 mm, P < 0.001), and longer procedure time (181.94 ± 70.02 min, P < 0.001) were noted in LSPAF. After the first catheter ablation, the recurrence rate of AF was highest in LSPAF (Log Rank, P < 0.001). Larger left atrium diameters (LAD) ( P = 0.006; HR: 1.063; CI: 1.018–1.111) and NPV triggers ( P = 0.035; HR: 1.707; 1.037–2.809) independently predicted AF recurrence in LSPAF. Conclusions: Compared with PAF and PerAF, LSPAF had a higher incidence of NPV triggers and worse long-term outcome after catheter ablation. NPV triggers and LAD independently predicted AF recurrence after catheter ablation in LSPAF.